Innovative model of cooperation for small agricultural producers - Alexandru Iăpuşan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The present study has the objective to elaborate an innovative model of cooperation that can represent a general structural solution, beneficial to small agricultural producers, being one of the very few real solutions that can connect them to the agricultural market and to development resources. In the first part of the paper, it is presented a retrospective of the agricultural cooperation route in Romania. The prospects of agricultural cooperation are oriented toward directions and domains of agriculture, for that the innovative cooperation model proposed can represent the functional and advantageous solution for the small agricultural producer. By the interpretation of the RGA data, 2002, 2010, regarding agricultural holdings, corroborated with theoretical and legislative aspects, it was pursued to realize an analysis of the agriculture particularities from our country, highlighting the necesity to develop a cooperation structures (1-st degree cooperative) in agriculture. The perspective analysis of small farmers to join, can be interpreted starting from the questions (Who are the small producers?, Why must find a solution for them? What is their direction of evolution? Why do not associate?) relevant found in SWOT analysis of small individual farms. In the last part of the paper it is defined the legal framework for cooperation of small individual producers, in this context developing the innovative cooperation model, operating principles and conditions for this model to be viable.
Keywords: 330; innovative model of cooperation; agricultural cooperation; individual agricultural holdings; small agricultural producer